Japan's Heisei municipal mergers and the contradictions of neo-liberal administrative planning (2014)
This article addresses Japans Heisei period municipal mergers, which occurred from 2000 to 2010, considering the emerging outcomes and long-term implications. The mergers, which aimed to upscale on a national level to larger-sized municipalities while also rationalising administrative costs and streamlining services, reduced the number of municipalities in Japan from over 3000 to under 1800. Reports from prefectural and municipal bureaus and research institutions, together with coverage through the media, indicate that these aims have largely been met in the short term. However, these sources also indicate that resident reaction is less than favourable, particularly in terms of service rationalisation and loss of local identity. In terms of the long-term implications of the mergers as reflecting within Japan a transition from a developmental state policy orientation toward nation state liberalism, questions are emerging for rural areas regarding the long-term sustainability of the post-merger national municipal structures, as well as resident acceptance of the neo-liberal governing philosophy.
Keywords: Administrative structure - Japan; Municipalities - Japan; Local government - Japan; Local government